Nonocclusive Mesenteric Ischemia Associated with Ogilvie Syndrome. (7th September 2014) - Sakamoto, Takashi; Suganuma, Toshiyuki; Okada, Shinichiro; Nakatani, Kensuke; Tamaki, Sawako; Lefor, Alan T.
Abstract : Nonocclusive mesenteric ischemia (NOMI) is one type of acute mesenteric ischemia. Colonic pseudoobstruction, known as Ogilvie syndrome, is a disorder defined by colonic distension in the absence of mechanical obstruction. A relationship between these diseases has not yet been reported, based on a review of the literature. We report a patient with NOMI secondary to Ogilvie syndrome. An 82-year-old woman reported three days of intermittent abdominal pain. Plain computed tomography scan showed colonic obstruction at the rectosigmoid colon. Colonoscopy was performed that showed a large amount of stool and no evidence of tumor or other physical causes of obstruction. We diagnosed the patient with Ogilvie syndrome and continued nonoperative management. On the third hospital day, she complained of abdominal distension. A repeat CT scan showed pneumatosis intestinalis in the small bowel and ascending colon, with portal venous gas. Emergency laparotomy was performed with diagnosis of mesenteric ischemia. Intraoperatively, there were multiple skip ischemic lesions in the small intestine and cecum. We resected the ischemic bowel and performed a distal jejunostomy. Her residual small bowel measured just 20 cm in length. Postoperatively, her general status gradually improved. She was discharged with total parenteral nutrition and a small amount of enteral nutrition.